(untitled) (The Pakistan Development Review, 2012)
Capital market efficiency and the prediction of future stock prices are the most thought-provoking and ferociously debated areas in finance. The followers of traditional financial theory strongly believe that the markets are efficient in pricing the financial instruments. This view became popular after Fama’s work on the Efficient Market Hypothesis. But before 1990s, wide-ranging financial literature documented that stock prices, to some extent, are predictable. Many psychologists, economist and the journalists are of the view that general tendency of individuals is to overreact to the information. De Bondt and Thaler (1985) studies this view of experimental psychology that whether such behaviour matters at the market level or not. They found out that stock prices will overreact to information, and suggested that contrarian strategies buy the past losers and sell the past winners, earn abnormal returns. They extended the holding period from 3 to 5 years and provide the evidence of long term returns reversal. Jegadeesh (1990) and Lehmann (1990) supported the evidence of return reversal in short term, i.e. from one week to one month. They suggested that the contrarian strategies having holding period of one week to one month earned the significant abnormal return. Lo and Mac Kinalay (1990) objected on the ground that a major portion of this abnormal return, reported by Jegadeesh (1990) and Lehmann (1990), is due to the delayed reaction of stock prices to common factors rather than to overreaction. Some other researchers pointed out some other reasons of this abnormal stock returns i.e. short-term pressure on stock prices and absence of liquidity in the market rather than overreaction.